Quantitative Soundscape Analysis to Understand Multidimensional Features - Wilford, Dylan Charles; Miksis-Olds, Jennifer L.; Martin, S. Bruce; Howard, Daniel R.; Lowell, Kim; Lyons, Anthony P.; Smith, Michael James (Frontiers in Marine Science, 2021)
A methodology for the analysis of soundscapes was developed in an attempt to facilitate efficient and accurate soundscape comparisons across time and space. The methodology consists of a collection of traditional soundscape metrics, statistical measures, and acoustic indices that were selected to quantify several salient properties of marine soundscapes: amplitude, impulsiveness, periodicity, and uniformity. The metrics were calculated over approximately 30 h of semi-continuous passive acoustic data gathered in seven unique acoustic environments. The resultant metric values were compared to a priori descriptions and cross-examined statistically to determine which combination most effectively captured the characteristics of the representative soundscapes. The best measures of amplitude, impulsiveness, periodicity, and uniformity were determined to be SPLrms and SPLpk for amplitude, kurtosis for impulsiveness, an autocorrelation based metric for periodicity, and the Dissimilarity index for uniformity. The metrics were combined to form the proposed “Soundscape Code,” which allows for rapid multidimensional and direct comparisons of salient soundscape properties across time and space. This initial characterization will aid in directing further analyses and guiding subsequent assessments to understand soundscape dynamics.